The effects of hygroscopicity on ice nucleation of fossil fuel combustion aerosols in mixed-phase clouds - Y. Yun; J. E. Penner; O. Popovicheva (Atmospheric Chemistry and Physics, 2013)
Fossil fuel black carbon and organic matter (ffBC/OM) are often emitted together with sulfate, which coats the surface of these particles and changes their hygroscopicity. Observational studies at cirrus temperatures (≈−40 °C) show that the hygroscopicity of soot particles can modulate their ice nucleation ability. Here, we implement a scheme for 3 categories of soot (hydrophobic, hydrophilic and hygroscopic) on the basis of laboratory data and specify their ability to act as ice nuclei at mixed-phase temperatures by extrapolating the observations using a published deposition/condensation/immersion freezing parameterization. The new scheme results in significant changes to anthropogenic forcing in mixed-phase clouds. The net forcing in our offline model studies varies from 0.111 to 1.059 W m−2 depending on the ice nucleation capability of hygroscopic soot particles. The total anthropogenic cloud forcing and whole-sky forcing with the new scheme are 0.06 W m−2 and −2.45 W m−2, respectively, but could be more positive (by about 1.17 W m−2) if hygroscopic soot particles are allowed to nucleate ice particles. The change in liquid water path dominates the anthropogenic forcing in mixed-phase clouds.